A dictionary of science - Daintith, John; Martin, E. A. (Oxford University Press, 2005)
It provides comprehensive coverage of biology (including human biology), chemistry, physics, the earth sciences, and astronomy. The entries are supported by over 200 clear diagrams and illustrations, and fully cross-referenced for ease of use.
Keywords: Science -- Dictionaries.; elektronické knihy; electronic books